2021
DOI: 10.1002/ar.24617
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of human labial glands in response to cevimeline treatment

Abstract: Among the pathologies affecting the salivary glands, the Sjögren's syndrome (SS), an autoimmune disease, causes progressive destruction of the glandular tissue. The effect of SS is particularly evident on the labial glands and the morphological analysis of these minor glands is considered useful for diagnosis. Cevimeline hydrochloride (SNI), a selective muscarinic agonist drug, is one of the elective treatments for the hyposalivation due to SS, acting not only on major salivary glands, but also on labial gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The samples were immediately cut and placed in a dish with or without cevimine medium for comparison. According to this study, cevimeline causes secretion in the labial glands, and its impact is more physiological than that of pan-muscarinic agonists [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The samples were immediately cut and placed in a dish with or without cevimine medium for comparison. According to this study, cevimeline causes secretion in the labial glands, and its impact is more physiological than that of pan-muscarinic agonists [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal and human studies demonstrated that the duration of cevimeline-induced salivation was twice as long as that of pilocarpine [175]. Loy et al [176] confirmed that the administration to humans increased salivary gland secretion from the buccal glands based on findings obtained using optical and electron microscopies. The recommended dose of cevimeline for xerostomia in SS patients is 30 mg orally three times a day.…”
Section: Cevimelinementioning
confidence: 95%